Ecosystem Restoration – A Holistic Approach - GNANASEKARAN S (PREPARE@u® | IEI Conferences, 2021)
The Ecosystem restoration is highly need of the hour as survival of our future generation to some extent depends on if ecosystem is properly restored. In stratosphere, ozone layer (O3) is rapidly depleting and thus forming holes in the ozone layer, pollution of troposphere (O2), Pollution of Land by mindless application of toxic chemical fertilizers & pesticides, merciless dumping of trash in to all water bodies like ponds, lakes, rivers, canals and drains as well as in to Ocean, uncontrollable emissions in to air, excess radiation emanation from communication towers beyond tolerable limit, littering on roads and streets, mercilessly cutting of big  age old trees  in mass numbers on the name of road widening projects etc.  All the above caused maximum damage to the Ecosystem and the result is evident like Greenhouse effect, Global Warming, premature glacier melting in polar and hill regions (Cryosphere damage), torrential rains in unusual manner, drought etc.